EVALUASI TUGAS TUTOR DALAM PROSES PEMBELAJARAN PAKET B DI PKBM HARAPAN BANGSA, KECAMATAN TAMBANG, KABUPATEN KAMPAR - Hillery Andam Dewi; Wilson Wilson; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is an evaluation research with a formative evaluation type that uses a naturalistic qualitative approach that aims to provide a systematic description of the evaluation of tutor assignments in the learning process of package B in PKBM Harapan Bangsa. This research was conducted at PKBM Harapan Bangsa, Kecamatan Tambang, Kabupaten Kampar and involved 3 informants who were used as resource persons, including tutors as core informants I and core informants II, and managers of PKBM as control informants. The results of this study indicate that the tutor performs his duties in the learning process of package B in PKBM Harapan Bangsa in accordance with the Guidelines for the Implementation of Equality Education Package B (2012: 7) This can be seen from the implementation of tutor assignments starting from planning such as preparing lesson plans, conducting activities learning administration. Implementation of learning such as managing the learning process, choosing methods and implementing learning in accordance with the realm to be achieved, motivating students, choosing to develop or develop media / teaching materials and Conduct an assessment in the learning process. The results of the evaluation of tutor assignments in the learning process of package B in PKBM Harapan Bangsa are that the tutors are considered good in doing their work in the learning process.Key Words: Evaluation, Tutor Task, Learning Process, Package B